Transcriptional Mechanisms Controlling miR-375 Gene Expression in the Pancreas. (20th June 2012) - Avnit-Sagi, Tali; Vana, Tal; Walker, Michael D.
Abstract : MicroRNAs (miRNAs) are a class of small non-coding RNAs that play an important role in mediating a broad and expanding range of biological activities. miR-375 is expressed selectively in the pancreas. We have previously shown that selective expression of miR-375 in pancreatic beta cells is controlled by transcriptional mechanisms operating through a TATA box-containing promoter. Expression of miR-375 has been reported in non-beta cells within the endocrine pancreas, and indeed inactivation of miR-375 leads to perturbation in cell mass and number of both alpha and beta cells. Consistent with its expression throughout the endocrine pancreas, we now show that the promoter of the miR-375 gene shows selective activity in pancreatic endocrine alpha cells, comparable to that observed in beta cells. We previously identified a novel negative regulatory element located downstream of the miR-375 gene transcription start site. By generating luciferase reporter genes, we now show that the sequence is functional also when positioned upstream of a heterologous promoter, thus proving that the repressor effect is mediated at least in part at the level of transcription. Further characterization of the transcriptional control mechanism regulating expression of miR-375 and other pancreatic miRNAs will contribute to a better understanding of pancreas development and function.